Pāḷaka sahacara : = Pastor's companion - Rath, Gangadhar; Rath, Gangadhar; Osgood, W. C.; Osgood, W. C. (Printed at the Orissa Mission Press, for the Christian Literature Committee, Utkal Christian Council, 1954)
Forms of service for general worship, festivals, baptism, Lord's supper, marriage and burials